Effect of Using Different Types of Binder on the HA Foam Properties - HAMIZI, MUHAMMAD FARHAN BIN HAMIZI; Mat Noor, Fazimah (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study investigates the impact of double sintering on the properties of porous hydroxyapatite (HA) structures, which were fabricated using the replication method. Hydroxyapatite is a widely used biomaterial due to its biocompatibility and similarity to the mineral phase of natural bone. The replication method involves creating porous structures that mimic natural bone tissue. The objectives of this research were to assess the structural and mechanical properties of porous HA and to determine whether double sintering can enhance these properties. The double sintering process involves subjecting the porous HA samples to two separate sintering steps, potentially improving densification and crystallinity. Methods included the fabrication of porous HA samples using the replication method, followed by a single sintering and double sintering process. The samples were characterized using techniques such as X-ray diffraction, scanning electron microscopy, and mechanical testing to assess changes in crystallinity, microstructure, and mechanical strength. Results show that double sintering had a significant impact on the properties of the porous HA. It led to improved densification compared to the single sintering process. Additionally, including compressive strength were also enhanced in the double- sintered samples. In conclusion, this study demonstrates that double sintering is an effective technique to enhance the properties of porous hydroxyapatite fabricated by the replication method. These improvements in structural and mechanical properties make double sintering a promising method for producing biomaterials with better suitability for bone tissue engineering and other biomedical applications.